2014
DOI: 10.4236/fns.2014.54039
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enrichment of Baobab Fruit Pulp Treated with Oil Extracted from the Seeds

Abstract: The effect of the application of oil from baobab seeds on the antioxidant capacity and stability of ascorbic acid in the fruit pulp at varying temperature were evaluated. Ascorbic acid analysis of the fruit pulp revealed that the concentration in the raw extract of the pulp sullied rapidly matched with the extract treated with the seed oil. Compared with the raw extracts the formulated fruit pulp presented the highest concentration of the total ascorbic acid when both samples were subjected to varying temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…These trees produce large fruits that contain dry pulp particularly rich in minerals, vitamin C, and protein, and many kidney‐shaped seeds. The number and size of seeds vary from one species to another (from 40 to 150 seeds/fruit for a mass of 360 – 1700 mg/seed) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These trees produce large fruits that contain dry pulp particularly rich in minerals, vitamin C, and protein, and many kidney‐shaped seeds. The number and size of seeds vary from one species to another (from 40 to 150 seeds/fruit for a mass of 360 – 1700 mg/seed) …”
Section: Introductionmentioning
confidence: 99%
“…Whilst these seeds also contain minerals and proteins, they are mostly oleaginous with a fat content of 8 – 47%, depending on the species . Baobab oil is almost colourless, flavourless and fluid at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that baobab is a nutrient rich fruit which has ascorbic acid, riboflavin, niacin, pectin and citric, malic and succinic acids, while the oil also comprises the vitamins D, E and A (Besco et al,2007, Donkor et al, 2014. The pulp of A. digitata is a l s o rich in dietary fibers (Ibrahima et al,2013).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine baobab fruit pulp is used in the treatment of fevers, diarrhea and malaria. Due to its high vitamin C content, baobab fruit pulp has a well-documented antioxidant capacity [1].…”
Section: Introductionmentioning
confidence: 99%